ESCHERICHIA COLI BACTERIA AND THEIR RESISTANCE PATTERN TO ANTIBIOTICS IN THE MATERNITY AND CHILDREN’S HOSPITAL/BABYLON - Mohammed, Jafar Saad Abdul Redha; Shaheed, Ali Hamza Mohammed; Ali, Ahmed Mohammed Abed; Mohammed , Ahmed Raad Abdul Redha; Yousef, Mohamed Waleed Ahmed (PT. Antis International Publisher, 2024)
This study focused on collecting urine samples from the midstream of urinary tract from patients with urinary tract infection (UTI). It was clear that E. coli isolates dominated the rest of the isolates due to their importance in causing urinary tract infection in women and men. To achieve this goal, 100 midstream urine samples were collected from patients suffering from urinary tract infection in Maternity and Children's Hospital/Babylon from men and women for the period from 11/11/2018 to 1/11/2019. These samples were cultured on eosin medium and solid MacConkey medium to confirm the diagnosis. The disk diffusion method was used to test the sensitivity of the isolates of this bacterium to a number of antibiotics (18 antibiotics) used as treatments. The most important results are summarized as follows: 1. Isolation and diagnosis of 72 isolates carrying the characteristics of E. coli bacteria, with infection predominance in women (60 cases) more than men (19 cases). All E. coli isolates are resistant to antibiotics that affect the cell wall